Hypoparathyroidism: what is the best calcium carbonate supplementation intake form? - Loraine Gollino; Maria Fernanda Giovanetti Biagioni; Nathalia Regina Sabatini; José Vicente Tagliarini; José Eduardo Corrente; Sérgio Alberto Rupp de Paiva; Gláucia Maria Ferreira da Silva Mazeto (Brazilian Journal of Otorhinolaryngology, 2019)
Introduction: In hypoparathyroidism, calcium supplementation using calcium carbonate is necessary for the hypocalcemia control. The best calcium carbonate intake form is unknown, be it associated with feeding, juice or in fasting. Objective: The objective was to evaluate the calcium, phosphorus and calcium × phosphorus product serum levels of hypoparathyroidism women after total thyroidectomy, following calcium carbonate intake in three different forms. Methods: A crossover study was carried out with patients presenting definitive hypoparathyroidism, assessed in different situations (fasting, with water, orange juice, breakfast with a one-week washout). Through the review of clinical data records of tertiary hospital patients from 1994 to 2010, 12 adult women (18-50 years old) were identified and diagnosed with definitive post-thyroidectomy hypoparathyroidism. The laboratory results of calcium and phosphorus serum levels dosed before and every 30 min were assessed, for 5 h, after calcium carbonate intake (elementary calcium 500 mg). Results: The maximum peak average values for calcium, phosphorus and calcium × phosphorus product were 8.63 mg/dL (water), 8.77 mg/dL (orange juice) and 8.95 mg/dL (breakfast); 4.04 mg/dL (water), 4.03 mg/dL (orange juice) and 4.12 mg/dL (breakfast); 34.3 mg2/dL2 (water), 35.8 mg2/dL2 (orange juice) and 34.5 mg2/dL2 (breakfast), respectively, and the area under the curve 2433 mg/dL min (water), 2577 mg/dL min (orange juice) and 2506 mg/dL min (breakfast), 1203 mg/dL min (water), 1052 mg/dL min (orange juice) and 1128 mg/dL min (breakfast), respectively. There was no significant difference among the three different tests (p > 0.05). Conclusion: The calcium, phosphorus and calcium × phosphorus product serum levels evolved in a similar fashion in the three calcium carbonate intake forms. Resumo: Introdução: No hipoparatireoidismo, a suplementação de cálcio com carbonato de cálcio é necessária para o controle da hipocalcemia. A melhor forma de ingestão de carbonato de cálcio ainda é desconhecida, seja concomitante com alimentação, no suco ou em jejum. Objetivo: Avaliar os níveis séricos de cálcio, fósforo e produto cálcio-fósforo em mulheres pós tireoidectomia por hipoparatireoidismo, após a ingestão de carbonato de cálcio em três formas diferentes. Método: Foi realizado um estudo cruzado em pacientes com hipoparatireoidismo definitivo, avaliados em diferentes situações (em jejum, com água, suco de laranja, café da manhã, após washout de uma semana). A revisão dos prontuários dos pacientes de um hospital terciário de 1994 a 2010 identificou 12 mulheres adultas (18-50 anos), diagnosticadas com hipoparatireoidismo definitivo pós-tireoidectomia. Os resultados laboratoriais dos níveis séricos de cálcio e fósforo foram mensurados antes e a cada 30 minutos durante 5 horas, após a ingestão de carbonato de cálcio (cálcio elementar 500 mg). Resultados: Os valores de pico máximo médio de cálcio, fósforo e produto cálcio-fósforo foram 8,63 mg/dL (água), 8,77 mg/dL (suco de laranja) e 8,95 mg/dL (café da manhã); 4,04 mg/dL (água), 4,03 mg/dL (suco de laranja) e 4,12 mg/dL (café da manhã); 34,3 mg2/dL2 (água), 35,8 mg2/dL2 (suco de laranja) e 34,5 mg2/dL2 (café da manhã), respectivamente, e a área sob a curva foi 2.433 mg/dL.min. (água), 2.577 mg/dL.min. (suco de laranja) e 2.506 mg/dL.min. (café da manhã), 1.203 mg/dL.min. (água), 1.052 mg/dL.min. (suco de laranja) e 1.128 mg/dL.min. (café da manhã), respectivamente. Não houve diferença significante entre os três diferentes testes (p > 0,05). Conclusão: Os níveis séricos de cálcio, fósforo e produto cálcio-fósforo evoluíram de forma semelhante nas três formas de ingestão de carbonato de cálcio. Keywords: Calcium, Calcium carbonate, Hypoparathyroidism, Phosphorus, Thyroidectomy, Palavras-chave: Cálcio, Carbonato de cálcio, Hipoparatireoidismo, Fósforo, Tireoidectomia